REVITALISASI ANGKUTAN UMUM UNTUK MENGURANGI KEMACETAN JAKARTA - Sonya Sidjabat (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
People live in Jakarta, called as Jakartans by the Jakarta Post, like to use private vehicles due to low maintaining budget especially for motorcycle. This evidence creates a trend of increasing private vehicles nowadays which impacts on the traffic jam. This phenomenon affects the decreasing use of public transportation which creates the decreasing number of public transportation every year. Based on the statistics, the number of public transportation in 1980’s was 50 % of the whole vehicles. However, in 2010 it was decreasing much on 12, 9 % only. The government was asked to revitalize the management of public transportation in Jakarta and apply the regulation especially for those who against it. These two steps were thought to be a great solution for the safety and convenience of Jakartans. This study used qualitative and library research.